Stock Returns of Pharmaceutical Companies during COVID-19 - Ajeng Aprilyana Pratiwi; Diyah Santi Hariyani; Wenni Wahyuandari; Eni Minarni (AJAR, 2023)
The Covid-19 pandemic has had a major impact on the share prices of companies in Indonesia, while the sector that received positive sentiment amid the Covid-19 outbreak is the Pharmaceutical Company Sector. The purpose of this study is to analyse the effect of earning per share, financial performance, and stock liquidity on stock returns during the Covid-19 pandemic (a case study on a pharmaceutical company listed on the Indonesia Stock Exchange). The method used in this study is quantitative. The source of data used in this study is secondary data. The sampling technique used in this research is the purposive sampling technique. This study indicates that return on equity has a significant effect on stock returns. Earnings per share and stock liquidity have no impact on stock returns.